Epistemology of Islamic Education Al-Jabiri Perspective of the Conservative-Modernist-Neo Modernist Flow and Burhani-Bayani-Irfani - Sigit Tri Utomo; Nur Alfi Mu’anayah (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2020)
This research is a qualitative study using a library approach, the object is the epistemology of Islamic education, conservative-modernist-neo-modernist and burhani-bayani-irfani. The data collection method in this research uses literature study. In this stage, the researcher tries to select data (books) in the epistemology of Islamic education, conservative-modernist-neo-modernist and burhani-bayani-irfani. In this writing, the analysis used with hermeneutics, namely the author explains that behind the text there is context meaning or behind the explicit meaning there is an explicit meaning if interpreted literally can be interpreted as an interpretation or interpretation of the epistemology of Islamic education, conservative-modernist-neo-modernist and burhani-bayani- irfani. The author also uses content analysis, namely research conducted on information documented in recordings, both images, sounds, writing and others. With this method, data analysis and scientific processing will be carried out on the epistemological content of Islamic education, the conservative-modernist-neo-modernist and burhani-bayani-irfani schools. The results showed that science continues to develop throughout the history of thought such as rational flow of viewing educational activities as actualizing the potentials of individuals so that according to this flow the essence of education is the transformation of various potential potentials into actual abilities. The success of the transformation of the various potentials that exist in this rational flow, is largely determined by how much the optimization of the functions of sense powers and ratios. Baby epistemology is an epistemology that emphasizes the authority of the text as an indicator of truth. Reason in this epistemology is only as a support text and does not have a good space or in other words lower when compared to the text. In object Bayani tradition can be seen in fiqh. Second, Burhani epistemology is knowledge gained from demonstrative analogies which in this case gives the role of reason and senses in human beings. Third, the epistemologist irfani is knowledge gathered from the human heart.